Sariling likha ([Manila] Philippine Information Agency)
Shows the skills and creativeness of the Filipino people in profitable activities, like buri-hat making, basketry, weaving, pottery, ceramic crafts, etc.
VHS
Keywords: Handicraft -- Philippines; Small scale industry